Analisis Semiotika Pesan Dakwah Bunda Aniqq Alfaqiroh dalam Streaming YouTube “TERAPI MEMAAFKAN” - Romadlany, Zakiyah; Nazilah, Solihatun (Instructional Development Journal, 2025)
Abstract: In today's digital era, technology has made it easier for people to share and access various types of information, including the dissemination of Islamic teachings or dakwah. YouTube has become one of the platforms that provide opportunities for preachers to convey Islamic teachings in a more creative and engaging way for audiences. One prominent figure in digital dakwah is Bunda Aniqq Alfaqiroh, who, through YouTube streaming on PPA Institute, delivers content with themes of spiritual motivation. This study aims to analyze dakwah messages in the YouTube streaming titled "THERAPY OF FORGIVENESS" using a descriptive qualitative approach and Ferdinand de Saussure’s semiotic analysis method. The analysis is conducted by identifying the signifier, which includes the visual and audio elements used to convey the message, and the signified, which refers to the underlying meanings. The findings of the study reveal that dakwah messages in the YouTube streaming "THERAPY OF FORGIVENESS" are conveyed through various verbal and non-verbal symbols, such as music, facial expressions, voice intonation, and video visualization, which function as signifiers. Meanwhile, the interpreted meanings (signified) emphasize Islamic values regarding the importance of forgiveness, inner peace, and spiritual motivation to live life with sincerity. With the continuous growth of digital media, this study is expected to serve as a reference for preachers and content creators in optimizing digital platforms as a broader and more effective means of dakwah.